Partnerships for Capacitation and Promotion of Sustainable Agricultural Mechanization (SAM) in Ghana - Amankwaa-Yeboah, Patricia; Dalaa, Mustapha Alasan; Tepa-Yoto, Ghislain; Mkomwa, Saidi; Yeboah, Stephen; Amponsah, Shadrach K.; Keteku, Agbesi K.; Kyere, Reginald; Waldmann, Kaja; Kariuki, Philip Wanjohi; Bourarach, El Hassane; Kienzle, Josef (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The adoption of sustainable agricultural mechanization (SAM) can sustainably increase productivity, and increase ecosystem resilience. Thirty (30) baby trials and One mother trial were established to expand access to smallholder farmers to SAM technologies and generate and share scientific evidence on the performance of SAM technologies, services and information in Ghana. The demonstration trials utilize participatory research and extension approaches by using existing partnerships. The technology bundle consists of improved SAM technologies such as Ripping, Jab planter, Direct seeding, no-till farming combined with improved maize and cowpea seed, vine technology and horizontal staking. These were piloted alongside conventional farming as ploughing, hand seeding, farmer maize and cowpea variety, mounding and farmer staking. The multi-stakeholder workshop held bring together representatives from the public and private sectors to deliberate on issues concerning the development and promotion of sustainable agricultural mechanization (SAM) in Ghana. The workshop identifies models for the promotion of SAM technologies and the roles stakeholders play along the value chain to harness the potential through partnership building and linkages to end users. The workshop brings to bear interventions that can allow farmers and end users access to sustainable agricultural mechanization technology to considerably improve soil health and crop productivity. It also proposes innovative business and financing models, and systems for SAM technology development, and advocates for policy-enabling environments that can support and promote SAM. It also makes recommendations for the promotion and adoption of models, systems, and frameworks for SAM (i.e. creating an enabling environment for the development, promotion, and adoption of SAM). The workshop also discussed FAO’s Frameworks for Sustainable Agricultural Mechanization in Africa and highlighted action points that can effectively adopted to promote and scale sustainable agricultural mechanization in Ghana. Finally, the report highlights the need to ensure Gender and Youth Responsiveness of SAM technologies and innovations and a roadmap to harness stakeholder contributions towards the development and promotion of SAM.